The patchwork perspective: A new view for patient experience - Jason Wolf (The Beryl Institute, 2017)
As Patient Experience Journal has continued to contribute to the expanding patient experience conversation, we too recognize this has been a significant year of progress for the patient experience movement. This progress has emerged in a number of ways in research, practice and programs that reveal a comprehensive and integrated approach is now more than ever a central consideration in a commitment to experience. This idea of interwoven efforts, begins to frame an image - a patchwork of clear, critical and comprehensive pieces that while operating distinctly each have value, yet when bringing them together have an exponential opportunity to impact healthcare. The case here in raising the imagery of a patchwork is to acknowledge both the chaos and beauty of healthcare, recognize the individuality of various efforts and their power in coming together and to make the case that under this umbrella of experience we can create powerful alignment and purposeful grounding for focused action in moving forward. The idea that experience is the soft stuff of healthcare must come to an end for as intricate and challenging as the science of healthcare is, there may be no more complex opportunity than that of tackling the human experience in healthcare overall.